Where Were the Directors? - World Bank (Washington, DC, 2012)
The credit crisis has caused a cataclysm in corporate governance circles. Distinguished professors, leaders of industry, regulators, legislators and blue ribbon panels around the world are examining everything from bank regulation to how individuals relate to society. There are more "big ideas" floating around than ever. Most, of course, will come into the world with a bang, only to be forgotten equally quickly. Into this unsettled, shifting landscape, David Beatty takes a different approach. Rather than one big idea, Beatty proposes a series of concrete, common-sense methods to improve the effectiveness of Boards of Directors. These are improvements born of the current context, but which seem timeless. Much in the same way that a magician's trick seems obvious once you know how it is done, Beatty's suggestions seem absolutely intuitive once read, yet few boards now practice them. Beatty's prescriptions divide into three parts: 1) equipping boards with adequate expertise to deal with today's complex issues; 2) managing the time of Directors more efficiently so as to allow true strategic planning; and 3) bridging the expertise chasm between Managers and Directors. Those are all long-standing issues, what makes Beatty's advice valuable are the specific steps he recommends to achieve them.